Electrically induced spectral and spatial instabilities of photoresponse CdZnTe crystals - Mygal, V.P.; Phomin, A.S. (Functional Materials, 2006)
The features of I = f(λ) and I = f(x) dependences in Cd₁-ₓZnₓТе crystals containing a variety of two-dimensional structural defects, which become manifested under simultaneous action of biasing and modulating fields, have been exposed and explored. Basing on comparison of spectral and coordinate photocurrent dependences and their wavelet-spectrograms obtained at appropriate polarity, frequency, and on-off time ratio characteristics of the modulating square pulse voltage, an relation has been found between certain wavelength ranges of spectral instability and coordinates of structural defects aggregates originating those waves. Выявлены и исследованы особенности зависимостей I = f(λ) и I = f(x) кристаллов
Cd₁-ₓZnₓТе, содержащих двумерные дефекты структуры, которые проявляются при одновременном воздействии смещающего и модулирующего полей. На основе сопоставления спектральных и координатных зависимостей фототока и их вейвлет-спектрограмм, полученных при соответствующих полярности, частоте и скважности модулирующего П-образного напряжения, установлена связь между определенными диапазонами длин волн спектральной неустойчивости и координатами порождающих их ансамблей дефектов структуры. Виявлено i дослiджено особливостi залежностей I = f(λ) та I = f(x) для кристалiв
Cd₁-ₓZnₓТе, що мiстять двовимiрнi дефекти структури, якi виявляються при одночаснiй дiї змiщувального та модулювального полiв. На основi зiставлення спектральних i координатних залежностей фотоструму та їх вейвлет-спектрограм, одержаних при вiдповiдних полярностi, частотi та вiдноснiй тривалостi прямокутних iмпульсiв модулювальної напруги, встановлено зв'язок мiж певними дiапазонами довжин хвиль спектральної нестiйкостi та координатами ансамблiв дефектiв структури, що їх породжують.